UPGRADED SCIENTIFIC ORHODONTIC SIMULATOR WITH TEMPERATURE CONTROL AND THERMOCHAMBER - Radu Mircea Pisc; Anne Marie Rauten; Roxana Marinescu; Horia Octavian Manolea (Romanian Journal of Oral Rehabilitation)
Introduction There are many orthodontic simulators known as Typodonts used since 1981. We use in daily practice electrodonts by Savaria-Dent Kft (Szombatheley, Hungary), a laboratory device, which simulates the orthodontic movements. The electrodonts were created by setting the teethes in a silicone mould filled with dual consistency wax. Every tooth is wrapped in coper coil and continuous electric current is injected, heating the wax generating orthodontic movement under the action of orthodontic wires. This device comes with a time regulator and the amperage is limited to 2 Amps. The electrodont must be under direct supervision of the user because the heat inducted by copper in the wax will over melt the wax resulting complete destruction of the electrodont and subsequent failure in obtaining the results of the treatment performed on electrodont. Aim of the study Primary goal of this study was to evolve an orthodontic simulator for scientific and didactic use. The system developed in this study has the added benefit of tooth of time and visual movement quantification, increasing students understanding and allowing the study of biomechanical principles and appliance design in order to obtain the replication of the case for head to head studies of different orthodontic wires from ultra-flexible to thermo activated ones. Secondary goal was to reduce the human intervention for reconfiguration of electrodonts due to loss of wax or complete damage by overheating. Materials and methods. We initiated a collaboration between Orthodontic Department and the Dental Materials Department University of Medicine and Pharmacy Craiova for a tool necessary to evaluate orthodontic treatment with fixed appliance systems for scientific and didactic means. We aimed to reduce the time lost in laboratory to readjust the electrodonts during othodontic treatment stages, also to reduce student failure when operating the electrodonts. Results In the laboratory, we upgraded the electrodont using a thermo chamber independent of ambient interferences, we placed in direct contact with the wax for each dental arch thermometer that measures directly the temperature and disconnect the influx of current in the device when the wax is overheating 25 degrees is the maximal reference. The active phase of orthodontic treatment is situated between 20 and 25 degrees Celsius. We assessed the upgraded electrodonts with the new configuration and the results were evaluated by Orthodontic Specialist and dental technician, without any evidence of melting wax and the treatment was continuous. Conclusions The electrodont is an incredible tool for didactic and scientific purposes, offering consistent and accountable results of simulated orthodontic treatment. The upgraded version is offering this experience without the delay caused by repairing, correcting the wax model, with the help of technicians and the danger of completely melting the wax if it is not supervised correctly.